2023
DOI: 10.1021/acs.jafc.2c07804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide and Its Induced Protein S-Nitrosylation on the Structures and In Vitro Digestion Properties of Beef Myofibrillar Protein

Abstract: This study aimed to investigate the effects of nitric oxide (NO) and its induced protein S-nitrosylation on the structures and digestion properties of beef myofibrillar protein (MP). The MP was treated with 0, 50, 250, 500, and 1000 μM concentrations of NO-donor S-nitrosoglutathione (GSNO) for 30 min at 37 °C. The results indicated that GSNO treatment significantly decreased the sulfhydryl contents whereas the carbonyl contents increased. Meanwhile, compared with the control group, the surface hydrophobicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…52 Generally, α-helix and βsheet are relatively ordered protein structures with high stability, whereas β-turned corners and random curls are disordered structures. 53 In the present study, the percentages of β-turned corners and random curls gradually decreased with increasing I, indicating that the order of the solution of MPs increased and the formation of more stable structures.…”
Section: Ionic Strength Evaluation and Solubility Of Mps The Salty Ch...supporting
confidence: 57%
“…52 Generally, α-helix and βsheet are relatively ordered protein structures with high stability, whereas β-turned corners and random curls are disordered structures. 53 In the present study, the percentages of β-turned corners and random curls gradually decreased with increasing I, indicating that the order of the solution of MPs increased and the formation of more stable structures.…”
Section: Ionic Strength Evaluation and Solubility Of Mps The Salty Ch...supporting
confidence: 57%
“…The difference in MP’s hydrophilic and hydrophobic properties suggest the change of amino acid microenvironment. The tryptophan fluorescence in protein is receptive to the change of microenvironment, so the tertiary structure of MP can be evaluated by monitoring tryptophan fluorescence intensity ( Feng, Yin, Zhou, Ma, & Zhang, 2023 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study in our lab showed that NO and its induced protein S-nitrosylation could also affect the digestion properties of beef myofibrillar protein by changing the physicochemical properties and conformation of protein. 31 In short, the increased activity of NOS induced by pre-slaughter transport stress may indicate a higher level of NO production in postmortem muscle, which then possibly influences various postmortem biochemistry via the S-nitrosylation pathway to mediate the development of meat quality.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previously, it has been noted that NO could mediate the process of lipid oxidation in both direct (as an activator of lipid oxidation) and indirect (as a terminator of free radical chain reaction) pathways, which might in turn influence the meat color. Recently, a study in our lab showed that NO and its induced protein S -nitrosylation could also affect the digestion properties of beef myofibrillar protein by changing the physicochemical properties and conformation of protein . In short, the increased activity of NOS induced by pre-slaughter transport stress may indicate a higher level of NO production in postmortem muscle, which then possibly influences various postmortem biochemistry via the S -nitrosylation pathway to mediate the development of meat quality.…”
Section: Resultsmentioning
confidence: 99%